Spectral Density of Cooper Pairs in Series Double Coupled Quantum Dots - Superconductor Josephson Junction - Kumar, Rajendra (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
We study the simple device of two laterally-coupled quantum dots, where one of quantum dot Connected with left superconductor lead and also connected right superconductor lead (QD1) and (QD2) are coupling to each other as Series quantum dots. The Spectral Density and Josephson current through this double quantum dots junction and formed between superconducting leads having s-wave symmetry of the superconducting order parameter is analysed. For this purpose, we have considered a renormalized Anderson model that includes the double coupled of the superconducting leads with quantum dots level and an attractive BCS-type effective interaction in superconducting leads. We have calculated the double-particle spectral function and Josephson current of the quantum dot, theoretical analysis.